Negociação de créditos de carbono e os papéis de seus diversos agentes: estudos de caso no Brasil - Koga, Eduardo Koiti (2007)
The increase of atmospheric pollutants has been appointed as one of the responsible for the climatic changes. Governments and international entities, as the United Nations - UN established the Kyoto s Protocol, with the definition of reduction s purpose of atmospheric pollutants with the creation of compensations mode and control of emissions, such as Reductions Certificates of Emissions or Carbon Credits - CC. These certificates are part of the Mechanisms of Clean Development, a flexibilization s way adopted for the Protocol. The research objectives identify and to understand which the paper of the involved agents in the negotiation of CC in Brazil, which the general characteristics of this Market and as the interactions and the relations between the involved agents occur. In the development of this research it was used the exploratory strategy aiming at an understanding about the subject, actual, but with diffuse information, considering the study of the Business Administration. The research was realized through by means of semi-structuralized interviews with the respondent-keys that exert its activities in companies that attendance in projects development that will originate these certificates of reductions of emissions of Gases of the Effect Greenhouse - GEG. These outsourcing companies have basic play in this market; because there is UN requirement of specialization and execution in the development of these projects